Implementasi Nilai-Nilai Sosial Masyarakat Marjinal sebagai Sumber Belajar Kontekstual dalam Pembelajaran IPS SMP - Fajar Wahyudi Utomo; Muhammad ilman Naafi'a; Achmad Siswanto; Hafizul Akbar; Fini Andrea Alyshia (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
Social Studies (IPS) learning at the Junior High School level is often trapped in textual mastery of concepts and rarely reaches the social realities experienced directly by students. This study aims to explore the social values of the marginal community in Kampung Tongkol, North Jakarta, and to formulate a model for its implementation as a contextual learning resource through Role Playing Cards (RPC) media in junior high school Social Studies. The study employed a qualitative approach using a case study method. Data were collected through in-depth interviews with three community informants and Social Studies teachers, observation, and documentation, then analyzed using the Miles and Huberman interactive model within the framework of social capital and contextual learning. The findings show that the Kampung Tongkol community possesses seven prominent social values: social empathy, solidarity, sympathy, tolerance, a sense of shared fate, simple living, and high adaptability. These seven values function as social capital that sustains residents' survival strategies amid urban economic constraints. These values are relevant for integration into the material on social interaction, diversity, social problems, and economics in grade VII and VIII Social Studies. Implementation is carried out through Role Playing Cards media designed to be simple, flexible, and resource-efficient, thereby bridging Social Studies concepts with students' social experiences while strengthening empathy, care, cooperation, and social awareness. This study contributes to the development of Social Studies learning based on the wisdom of marginal urban communities, which has rarely been used as a formal learning resource.